Traditional crops for household food security and factors associated with on-farm diversity in the Mountains of Nepal - Gauchan, Devendra; Joshi, Bal K.; Sthapit, Sajal; Jarvis, Devra I. (GON Ministry of Agriculture and Cooperatives, 2020)
Traditional crops play an important role in household food security and livelihood needs of mountain communities, while at the same time safeguarding crop biodiversity for future generations. This study aims to analyse socioeconomic, farmspecificagro-ecological and market factors influencing cultivation and maintenance of crop diversity in Nepal. It used sample surveys of 328 households from mountains of Humla, Jumla, Lamjung and Dolakha districts in 2015. The sample survey was supplemented with participatory rural appraisals, field monitoring visits and local stakeholder consultations. Tobit regression model was used to assess factors driving household decisions to allocate area for production and maintenance ofon-farm diversity. Farm maintenance of crop diversity was related to household food sufficiency level of traditional crops. Factors influencing on-farm crop diversity and household food security varied with the crops, and mainly related with farmers’ age, family size, farm size, agro-ecosystemand market factor. Future research and development interventions need to focus on diversity rich solutions and technologies tailored to specific crops, socioeconomic, market and farm-agroecology of the households enhancing household food security and management of mountain crop biodiversity.